High throughput methods applied in biomaterial development and discovery - Hook, Andrew L.; Anderson, Daniel G.; Langer, Robert; Williams, Paul; Davies, Martyn C.; Alexander, Morgan R. (Elsevier, 2010)
The high throughput discovery of new materials can be achieved by rapidly screening many different materials synthesised by a combinatorial approach to identify the optimal material that fulfils a particular biomedical application. Here we review the literature in this area and conclude that for polymers, this process is best achieved in a microarray format, which enable thousands of cell-material interactions to be monitored on a single chip. Polymer microarrays can be formed by printing pre-synthesised polymers or by printing monomers onto the chip where on-slide polymerisation is initiated. The surface properties of the material can be analysed and correlated to the biological performance using high throughput surface analysis, including time-of-flight secondary ion mass spectrometry (ToF-SIMS), X-ray photoelectron spectroscopy (XPS) and water contact angle (WCA) measurements. This approach enables the surface properties responsible for the success of a material to be understood, which in turn provides the foundations of future material design. The high throughput discovery of materials using polymer microarrays has been explored for many cell-based applications including the isolation of specific cells from heterogeneous populations, the attachment and differentiation of stem cells and the controlled transfection of cells. Further development of polymerisation techniques and high throughput biological assays amenable to the polymer microarray format will broaden the combinatorial space and biological phenomenon that polymer microarrays can explore, and increase their efficacy. This will, in turn, result in the discovery of optimised polymeric materials for many biomaterial applications.